An assessment of Customer perceptions towards the installation of smart water meters: the case of City Harare - Chidenga, Tafadzwa (Midlands State University, 2018)
The research was premised on the need to understand the perceptions of the citizens towards the installation of smart water meters in Harare. The introduction of smart water meters in 2013 has been marred with a number of challenges emanating from Non-governmental organisations (NGOs) arguments based on the fact that it’s robbing them of their constitutional rights and there is compromise to social justice. The research was guided by a number of objectives including interalia, to explore the levels of customer satisfaction with the portable pricing by the City of Harare and to understand the nature and extent of citizen engagement in the installation process. Quite a number of theoretical underpinnings were outlined in the course of the research. A number of scholarly views and opinions on the subject matter were reviewed. The researcher used mixed method as a research paradigm in order to get an in-depth understanding of the phenomenon. The research thus was anchored on both qualitative and quantitative methodologies. Primary data sources was collected through research instruments like interviews and questionnaires observations were used to gather data from the respondents in the field. Statistical package for social scientists student version 19 was used to analyse data. From the research, it was found out that City of Harare is still lacking in terms of engaging the citizens in terms of policy issues. The research also unearthed that the people of Harare are willing to be on board in the smart water meter introduction discourse. Generally, women were satisfied by the introduction of smart meters as compared to their men counterparts. Some of this research`s recommendations are that City of Harare should optimise on the citizen engagement before coming up with policies that have far reaching effects like the pre-paid water meters, a dedicated team of customer service personnel should be put in place at Council to interact with customers, and also that Council should come up with a new water tariff regime that gives residents a zeal to pay for the service provided.